Hubungan Problematic Internet Use Terhadap Kualitas Tidur Pada Mahasiswa - Ike Diah Ayu Putri Ningrum; Lia Aulia Fachrial (Inovasi Kesehatan Global, 2025)
This study aims to empirically examine the relationship between Problematic Internet Use and Sleep Quality among university students. This is a quantitative study that employs a bivariate correlation analysis method. The total number of respondents in this study was 106 individuals, consisting of 30 males and 76 females, aged between 18 and 23 years. The study used two scales as data collection instruments: a sleep quality scale and a Problematic Internet Use scale. The hypothesis was tested using bivariate correlation analysis to determine whether there is a significant relationship between sleep quality and Problematic Internet Use among students. The results support the hypothesis, indicating a significant positive relationship between Problematic Internet Use and sleep quality, with a significance value of p = 0.001 (p < 0.005) and a correlation coefficient of R = 0.227. This means that the higher the level of Problematic Internet Use, the better the sleep quality among students. Conversely, the lower the Problematic Internet Use, the poorer the sleep quality.